A Comparison of outcome between Transabdominal Preperitoneal (TAPP) and Lichtenstein operation for primary inguinal hernia repair – An institutional study - Rayamajhi, Bikash Bahadur; Basukala, Sunil; Thapa, Narayan; Ayer, Dhirendra; Karki, Saurav; Basukala, Bikram (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Inguinal hernia repairs are one of the most common operations in general surgery. Apart from the classical open repairs, minimally invasive approaches are increasingly preferred to manage groin hernia repair. However, the optimal surgical approach still remains controversial. Methods: This is a prospective observational study done in Shree Birendra Hospital, a 750- bedded tertiary care military hospital located in Kathmandu from July 2021 to December 2021. A total of 120 patients operated for inguinal hernia by either open Lichtenstein repair or Transabdominal Preperitoneal (TAPP) in the department of surgery were included in this study. Results: The mean age of patients between open Lichtenstein repair and TAPP was 59.3 (22-79) and 63.4 (27-70) years respectively. The majority of patients were male among both the groups constituting of more than 95%. The mean intraoperative duration among the two groups was 44.12±7.23 minutes and 77.43±8.77minutes, respectively (p=0.021). The mean postoperative pain was less in TAPP procedure compared to open procedure (p=0.037). The mean duration of the postoperative hospital stay was 2± 1.12 and 1±0.79 respectively. At the three-month evaluation, there were four cases of recurrence of which one of them underwent open procedure while three underwent TAPP procedure. Conclusion: Both the open Lichtenstein repair and the TAPP procedures are safe and effective in the repair of primary inguinal hernia. In a view of postoperative pain, seroma formation and length of hospital stay TAPP procedure has been found superior to open procedure in our study.